Factors associated with abandoning exclusive breastfeeding in Mexican mothers at two private hospitals - María Natividad Ávila-Ortiz; Ana Elisa Castro-Sánchez; Elizabeth Andrea Martínez-González; Georgina Mayela Núñez-Rocha; Adriana Zambrano-Moreno (BMC, 2020)
Abstract Background Exclusive breastfeeding (EBF) has multiple benefits for both the child and the mother; however, there is little data regarding the reason why Mexican mothers with a high socio-economic level abandon EBF before 6 months, and there is limited information about the practice of breastfeeding in private hospitals. The objective was to identify the factors associated with the cessation of exclusive breastfeeding in Mexican mothers at two private hospitals. Methods A cross-sectional study was conducted with 218 upper-class mothers selected according to their place of residence by geographic location, socio-economic level, and pediatric consultations cost. They were over 18 years old and with children aged 6 to 24 months. Data were collected between July and November 2016 by face to face interview using a structured questionnaire while the mothers waited for the pediatric postnatal care consultation in two private hospitals in northeastern Mexico. Exclusive breastfeeding was measured according to World Health Organization (WHO) recommendations, which consist of providing only breast milk for the first 6 months of life. Chi-squared tests and multivariate logistic regression were performed. Results Mean maternal age was 31.4 years (SD of 4.4) and most of the participants had an undergraduate education, were married, and worked outside the home. The prevalence of exclusive breastfeeding at 6 months was 28%. Upper-class working mothers are less likely to continue breastfeeding. There was a negative association with employment (AOR 13.69; 95% CI 1.59, 111.11), bottle use in the first 6 months (AOR 7.93; 95% CI 3.07, 20.48), and a low level of knowledge (AOR 2.18; 95% CI 1.04, 4.56). After 6 months, only 61 mothers (28%) maintained exclusive breastfeeding. Conclusions Knowledge level, bottle use, and employment are associated with premature cessation of EBF in Mexican upper-class mothers, attending two private hospitals. There was a high percentage of breastfeeding cessation in the sample. It is necessary to reinforce a strategy that coordinates the action of the different laws, regulations and programs affecting the exclusive breastfeeding practice, in order to adequately promote breastfeeding and support mothers in both public and private sectors.